Discovery Learning with Jigsaw II on Information Literacy and Cognitive Learning Outcomes of High School Students - Robiatul Adawiyah; Herawati Susilo; Sri Endah Indriwati (Jurnal Pendidikan Sains, 2019)
Abstract: This study aimed to determine the effect of the discovery learning model combined with Jig-saw II on the students’ information literacy and cognitive learning outcomes. The study was a quasi-experimental with a non-equivalent control group design. The subjects were 134 high school students divided into one group given discovery learning model combined with Jigsaw II and 3 control groups given discovery learning, Jigsaw II, or conventional learning model. The experiment showed that the discovery learning model combined with Jigsaw II resulting in significant differences in students’ information literacy and cognitive learning outcomes with Fvalue = 13.935 (p < 0.05) on information literacy F value = 6.527 (p < 0.05) on cognitive learning outcomes. It can be concluded that the discovery learning model combined with Jigsaw II significantly improved students’ information literacy and cognitive learning outcomes.Key Words: discovery learning, jigsaw II, information literacy, cognitive learning outcomesAbstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran discovery learning dipadu Jigsaw II terhadap literasi informasi dan hasil belajar kognitif. Penelitian merupakan penelitian eksperimen semu dengan desain nonequivalent control group design. Subjek yang digunakan yaitu siswa SMA sebanyak 134 siswa. Hasil penelitian menunjukkan nilai F sebesar 13,935 dan taraf signifikan sebesar 0,000<0,05 pada literasi informasi dan F sebesar 6,527 dan taraf signifikan sebesar 0,000<0,05 pada hasil belajar kognitif. Hal ini dapat disimpulkan bahwa ada perbedaan signifikan literasi informasi dan hasil belajar kognitif siswa yang menjalani model pembelajaran discovery learning dipadu Jigsaw II.Kata kunci: discovery learning, jigsaw II, literasi informasi, hasil belajar kognitif